Physical Exercise as a Therapeutic Approach for Patients Living with Type 2 Diabetes: Does the Explanation Reside in Exerkines?—A Review - Bernard, Daphné; Sultan, Ariane; Bouzakri, Karim (International journal of molecular sciences, 2025)
For a few decades, Type 2 Diabetes (T2D) has been recognized as a worldwide public health issue. T2D relies on systemic insulin resistance leading to Beta cell dysfunction. Nowadays, lifestyle modifications, such as improving eating habits and increasing physical activity, represent the first recommendations for managing T2D. Physical exercise, as a structured physical activity, is now considered as a non-pharmacological treatment with a wide range of beneficial effects, especially for people living with T2D. The review intends to summarize the current knowledge of physical exercise benefits in a context of T2D: from “unwanted” adipose tissue reduction to Beta cell health improvement. Moreover, we try to suggest an underlying mechanism explaining physical exercise beneficial effects in the context of T2D focusing on exerkines, molecules secreted in response to physical exercise. With this review, we highlight the beneficial impact of post-exercise secretions on Beta cell health and encourage research to continue in this direction. Identifying new exerkines with beneficial effects in the context of T2D could represent a promising approach for managing metabolic diseases.